SOSIALISASI SEDEKAH SAMPAH TERHADAP GERAKAN PEDULI LINGKUNGAN DI DESA SINGDANGSARI - Arif Prasetyo Aji; Nazriyah Nazriyah; Rini Endah Sugiharti; Deden Dicky Dermawan (Universitas Islam 45 Bekasi, 2023)
Research in scientific science is something that is familiar to students or students in the world of education. The objects and subjects of education are not only related to competence or human skills. One of the latest objects that really meet the topic of discussion is garbage. This topic does not only explain the form of waste, but how it is managed, technically, financially and the role of the community in different perceptions of the environment. Programs that make environmental care movements based on the identification of problems found. Waste Sedekahs are an alternative to maintaining a green and clean environment. In addition to having a positive impact, the Garbage Sedekah can also help the community's economy by collecting and separating the amount of organic and non-organic waste. This waste Sedekah program can turn unused items into very useful ones. Based on the identification of the problem, it was concluded that the Waste Sedekah program is a form of social engineering in bringing out innovations forcing people to change their perceptions and views about the environment and health.